Tadeusz Dzierżykray-Rogalski — w siedemdziesiątą rocznicę urodzin - Drozdowski, Zbigniew (Polskie Towarzystwo Antropologiczne, 1988)
The author presents the scientific output of professor Tadeusz Dzierżykray-Rogalski on his seventieth birth anniversary. The celebrator of the jub’iee was for many years a chairman of the Polish Anthropological Society, the editor of the Polish Anthropological Review, a worthy scientist of the Polish Anthropology and organizer of the scientific life.